Q-SINGLE VALUED NEUTROSOPHIC SOFT SETS - Tahir Mahmood; Qaisar Khan; Mohsin Ali Khan (Journal of New Theory)
In this paper, we have introduced the concept of Q-single value neutrosophic soft set, multi Qsingle valued neutrosophic set and defined some basic results and related properties. We have also defined the idea of Q-single valued neutrosophic soft set, which is the genralizations of Q-fuzzy set, Q-intuitionistic fuzzy set, multi Q-fuzzy set , Multi Q-intuitionistic fuzzy set, Q-fuzzy soft set, Q-intuitionistic fuzzy soft set. We have also defined and discussed some properties and operations of Q-single valued neutrosophic soft set